2023
DOI: 10.3389/fphar.2023.1230633
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide analysis of trigeminal ganglion and subnucleus caudalis in a mouse model of chronic constriction injury-induced trigeminal neuralgia

Xiaona Cui,
Bo Qin,
Chaoyun Xia
et al.

Abstract: Trigeminal neuropathic pain (TNP) induces mechanical allodynia and hyperalgesia, which are known to alter gene expression in injured dorsal root ganglia primary sensory neurons. Non-coding RNAs (ncRNAs) have been linked to TNP. However, the functional mechanism underlying TNP and the expression profile of ncRNAs in the trigeminal ganglion (TG) and trigeminal subnucleus caudalis (Sp5C) are still unknown. We used RNA sequencing and bioinformatics analysis to examine the TG and Sp5C transcriptomes after infraorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The majority of evidence comes from animal models of neuropathic pain that study injury to the spinal nerve. The cascade of events from peripheral to central in the nervous system result in major changes to neurons and their environment and may be affected by genetic variations [ 5 , 6 ].…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of evidence comes from animal models of neuropathic pain that study injury to the spinal nerve. The cascade of events from peripheral to central in the nervous system result in major changes to neurons and their environment and may be affected by genetic variations [ 5 , 6 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Recent studies have found missense mutations in both genes that encode the pore forming α1 subunit of the voltage-gated calcium channels, Cav3.1 and 3.2, resulting in gain of function and contributing to chronic pain [ 20 , 21 ]. Animal models of neuropathic pain involving chronic constriction injury of the infraorbital nerve have demonstrated that non-coding RNAs are involved in the development of trigeminal pain [ 6 , 22 ]. Following nerve injury, micro RNAs are downregulated in the dorsal root ganglion, which is thought to increase pain [ 23 ].…”
Section: Ion Channelsmentioning
confidence: 99%